Bcl-2△21 and Ac-DEVD-CHO Inhibit Death of Wheat Microspores - Sinha, Rakesh K.; Pospíšil, Pavel; Maheshwari, Priti; Eudes, François (Frontiers in Plant Science, 2016)
Microspore cell death and low green plant production efficiency are an integral obstacle in the development of double haploid (DH) production in wheat. The aim of the current study was to determine the effect of anti-apoptotic recombinant human B-cell lymphoma-2 (Bcl-2Δ21) and caspase-3-inhibitor (Ac-DEVD-CHO) in microspore cell death in bread wheat cultivars AC Fielder and AC Andrew. Induction medium containing Bcl-2Δ21 and Ac-DEVD-CHO yielded a significantly higher number of viable microspores, embryo-like structures (ELS) and total green plants in wheat cultivars AC Fielder and AC Andrew. Total peroxidase activity was lower in Bcl-2Δ21 treated microspore cultures at 96 h of treatment compared to control and Ac-DEVD-CHO. Electron paramagnetic resonance (EPR) study of total microspore protein showed a different scavenging activity for Bcl-2Δ21 and Ac-DEVD-CHO. Bcl-2Δ21 scavenge approximately 50% hydroxyl radical (HO•) formed, whereas Ac-DEVD-CHO scavenge approximately 20% of HO•. Conversely, reduced caspase-3-like activities were detected in the presence of Bcl-2Δ21 and Ac-DEVD-CHO, supporting the involvement of Bcl-2Δ21 and Ac-DEVD-CHO in increasing microspores viability by reducing oxidative stress and caspase-3-like activity. Our results indicate that Bcl-2Δ21 and Ac-DEVD-CHO protects cells from cell death following different pathways. Bcl-2Δ21 prevents cell damage by detoxifying HO• and supressing caspase-3-like activity, while Ac-DEVD-CHO inhibits the apoptotic pathways by modulating caspase-like activity.